Lobithelphusa mexicana Rodriguez, 1982 (Decapoda: Pseudothelphusidae): a reassessment of key characters and systematics - Villalobos-Hiriart, José Luis; Kamanli, Seyit A.; Álvarez, Fernando; Garbout, Amin; Clark, Paul F. (Zootaxa, 2019)
Lobithelphusa Rodriguez, 1982 is endemic to southern Mexico. Assigned to this monotypic genus is the freshwater pseudothelphusid crab, L. mexicana Rodriguez, 1982. The original description based on an old, dry, male specimen in the collections of the Natural History Museum, London, is brief and the crab was only partially figured. Lobithelphusa mexicana has subsequently never been recorded from Mexico and, consequently, the conservation status of this species is unknown. The type specimen has a complete, but detached left chela; is devoid of the left ambulatory pereiopods 1–3, with the fourth missing the carpus, propodus and dactylus; and its left first gonopod detached but retained in a glass tube kept adjacent to the crab. In spite of this damage the crab is still in remarkably good condition for a specimen registered in 1860. The purpose of this study is to apply computed tomography (CT) scanning techniques on the extant type, including its first gonopod, in order to provide detailed illustrations of the crab. These, in turn, shall be used to re-describe the species in order to help establish the current distribution status of L. mexicana in Mexico, and clarify its systematic position within the Pseudothelphusidae Ortmann, 1893.